2020
DOI: 10.3390/ijms21186506
|View full text |Cite
|
Sign up to set email alerts
|

An Iatrogenic Model of Brain Small-Vessel Disease: Post-Radiation Encephalopathy

Abstract: We studied 114 primitive cerebral neoplasia, that were surgically treated, and underwent radiotherapy (RT), and compared their results to those obtained by 190 patients diagnosed with subcortical vascular dementia (sVAD). Patients with any form of primitive cerebral neoplasia underwent whole-brain radiotherapy. All the tumor patients had regional field partial brain RT, which encompassed each tumor, with an average margin of 2.6 cm from the initial target tumor volume. We observed in our patients who have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 206 publications
(265 reference statements)
0
5
0
Order By: Relevance
“…This mechanism is similar to the changes caused by small vessel disease. Small vessel disease is largely associated with loss of arterial elasticity, markedly reduced arterial compliance, and reduced autonomic nervous system function, which leads to diffuse rarefaction of myelin sheaths, followed by axonal disruption and severe astrocyte gliosis 30 . These are suggested to cause disturbances in the interstitial fluid dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is similar to the changes caused by small vessel disease. Small vessel disease is largely associated with loss of arterial elasticity, markedly reduced arterial compliance, and reduced autonomic nervous system function, which leads to diffuse rarefaction of myelin sheaths, followed by axonal disruption and severe astrocyte gliosis 30 . These are suggested to cause disturbances in the interstitial fluid dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intact endothelial function is crucial for maintaining the integrity of the blood-brain barrier (BBB). Disruption of the BBB, as observed in WBI and γ-irradiationinduced microvascular injury [25][26][27][28][29][30][31][32][33], can lead to neuroinflammation and contribute to the genesis of cognitive impairment [34,35] (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining microvascular health is also crucial for preserving the integrity of the blood-brain barrier (BBB) [23,24]. Strong evidence suggests that WBI and γ-irradiation-induced microvascular injury contribute to BBB disruption [25][26][27][28][29][30][31][32][33], leading to neuroinflammation [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have clearly shown that cognitive impairment in fluency, working memory, and verbal memory can already be observed at 1-year follow-up after radiotherapy. 7 Furthermore, test scores were grouped into domains, which does not provide information on test specificity and sensitivity to detect more subtle cognitive changes. Additionally, the existing meta-analyses did not analyze the impact of potential practice effects.…”
mentioning
confidence: 99%